The Phenomenon of FOMO Defending Palestine: An Analysis of Surah Al-Hujurat Verse 10 from the Perspective of Tafsir An-Nuur - Nasrullah, Muhammad; Muhajirin, Muhajirin (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2024)
This study aims to examine the phenomenon of Fear of Missing Out (FOMO) in the context of defending Palestine through the study of Surah Al-Hujurat verse 10 from the perspective of Tafsir An-Nuur by T. M. Hasbi Ash-Shiddieqy. Surah Al-Hujurat verse 10 emphasizes the importance of brotherhood and peace among Muslims, which states that believers are brothers and must repair relations between those who are at odds and fear Allah in order to receive His mercy. The phenomenon of FOMO, which is often associated with the fear of missing out on important moments, can serve as a positive motivation in increasing Muslim participation in humanitarian actions and solidarity with the Palestinians. Tafsir An-Nuur emphasizes that brotherhood in Islam is not only spiritual but also social, which requires concrete action in helping brothers and sisters in need.This study uses a descriptive qualitative method with a literature approach to understand the relevance of this verse to social capital in Islam. The results show that FOMO can accelerate responses to humanitarian emergencies or crises, increase public participation and awareness, and ensure that contributions remain meaningful and sustainable. Thus, the FOMO phenomenon can be an encouragement for Muslims to actively engage in peace and solidarity efforts against Palestine, in accordance with the teachings of the Qur'an which emphasizes the importance of brotherhood and peace